Is it for generation me? A qualitative study exploring marketing and selling plants online to millennial-aged consumers - Lauri M Baker; Kelsey M Tully; Deanna R Sumners; Ernest Francis Jones; Andrés E León-Reyes; Cheryl Boyer; Hikaru H Peterson (Journal of Applied Communications, 2020)
As online selling of products like living plants increases, it is increasingly important to understand how millennial-aged consumers perceive the purchasing experience. New-media technologies like social media, e-newsletters, and other forms of digital communication are easily adopted by millennial-aged consumers. One of these tools, 360-degree video, offers novel ways to preview products offered online and look inside local brick-and-mortar stores, which can be visited in person. Sales of horticultural goods online have been slow to be developed by industry veterans, creating ample opportunities available to new ventures. This qualitative study used a series of three focus groups to answer the research questions of RQ1: What challenges exist for garden centers attracting millennials? RQ2: What are millennials preferences for purchasing live plants online? RQ3: What aspects of digital online marketing influence millennials to make decisions? RQ4: What are millennials preferences for 360-degree video? Results of this study indicate 360-degree video is not the preferred avenue for marketing plants online to millennials, however, high-quality photos and video with educational content and the use of social media could be effective.
Keywords: online selling; marketing; plants; 360-degree video; elaboration likelihood model